2009
DOI: 10.1007/s11262-009-0434-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Hungarian Maize dwarf mosaic virus isolates

Abstract: The genetic diversity of the coat-protein (CP) region and the untranslated C-terminal region (3'UTR) of Maize dwarf mosaic virus (MDMV) was analyzed to evaluate the variability between isolates (inter-isolate sequence diversity). The results of inter-isolate sequence diversity analysis showed that the diversity of the MDMV CP gene is fairly high (p-distance: up to 0.136). During sequence analysis, a 13 amino-acid residue insertion and an 8 amino-acid residue deletion were found within the N-terminal region of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…2b). All of these values exceed the criteria percentage, which in the case of potyviruses is 77 and 82 % identity at the nucleic acid and amino acid levels, respectively [36]. Thus, it can be concluded that these sequences are different isolates of the MDMV virus species.…”
Section: Virus Phylogeny and Genetic Distancementioning
confidence: 88%
“…2b). All of these values exceed the criteria percentage, which in the case of potyviruses is 77 and 82 % identity at the nucleic acid and amino acid levels, respectively [36]. Thus, it can be concluded that these sequences are different isolates of the MDMV virus species.…”
Section: Virus Phylogeny and Genetic Distancementioning
confidence: 88%
“…Potyviridae family, and remains among the most harmful viruses causing diseases of maize in various regions of the world, mostly in some Asian and European countries (Gell et al, 2010). More recently, infections of Maize chlorotic mottle virus (MCMV) (genus Machlomovirus, family Tombusviridae), transmitted by thrips, have been important in some countries (Silva-Rosales et al, 2015;Wangai et al, 2012).…”
Section: This Virus Is a Member Of The Potyvirus Genus Andmentioning
confidence: 99%
“…These include Sorghum mosaic virus (SrMV) [ 6 , 7 ], Johnsongrass mosaic virus (JGMV) [ 8 ], Maize chlorotic mottle virus (MCMV), and Maize chlorotic dwarf virus (MCDV) [ 9 ]. Among all the maize-infecting viruses, Maize dwarf mosaic virus (MDMV) is the most common disease agent in this monocotyledonous crop globally [ 10 ], with incidences of maize dwarf mosaic (MDM) disease reported in Africa, United States, Asia and Europe [ 11 ].…”
Section: Introductionmentioning
confidence: 99%